Screening of Genes Related to Early and Late Flowering in Tree Peony Based on Bulked Segregant RNA Sequencing and Verification by Quantitative Real-Time PCR - Xiaogai Hou; Qi Guo; Weiqiang Wei; Lili Guo; Dalong Guo; Lin Zhang (Molecules, 2018)
Tree peony (Paeonia suffruticosa Andrews) is a perennial woody shrub bearing large and colorful flowers. However, the flowering period is short and relatively uniform, which to an important extent hinders the cultivation and exploitation of ornamental peonies. In this study, the segregation of an F1 population derived from P. ostti ‘Feng Dan’ (an early-flowering cultivar) × P. suffruticosa ‘Xin Riyuejin’ (a late-flowering cultivar) was used to screen and analyze candidate genes associated with flowering period of the two parents. Extreme early- and late-flowering genotypes of the F1 population at full-bloom stage were sampled to establish an early-flowering mixed pool (T03), a late-flowering mixed pool (T04), a late-flowering male pool (T01), and an early-flowering female pool (T02), using the Sequencing By Synthesis (SBS) technology on the Illumina HiSeq TM2500 platform. A total of 56.51 Gb of clean reads data, comprising at least 87.62% of Quality30 (Q30), was generated, which was then combined into 173,960 transcripts (N50 = 1781) and 78,645 (N50 = 1282) unigenes, with a mean length of 1106.76 and 732.27 base pairs (bp), respectively. Altogether, 58,084 genes were annotated by comparison with public databases, based on an E-value parameter of less than 10−5 and 10−10 for BLAST and HMMER, respectively. In total, 291 unigene sequences were finally screened out by BSR-seq (bulked segregant RNA-seq) association analysis. To validate these unigenes, we finally confirmed seven unigenes that were related to early and late flowering, which were then verified by quantitative real-time PCR (qRT-PCR). This is the first reported study to screen genes associated with early and late flowering of tree peony by the BSA (bulked sample analysis) method of transcriptome sequencing, and to construct a high-quality transcriptome database. A set of candidate functional genes related to flowering time was successfully obtained, providing an important genetic resource for further studies of flowering in peony and the mechanism of regulation of flowering time in tree peony.